The Role of English and Technology on Human Performance in International Business - Cahya Budhi Irawan; Budi Sasongko; Imro'atul Afriani (International Journal of Applied Business and International Management, 2022)
Our aim is to investigate concepts in previous research regarding English Language Education through Human Performance and International Business. We used Content Analysis to compile scientific articles from Emerald, Science Direct and Korea Science as well as books written by experts in the field of English Education. We find that teachers and students alike must acquire sensitivity, emotional awareness, understanding of the teaching and learning process, and understanding of practical learning experiences. English can improve students' academic achievement and can improve their job prospects after graduation. English can also have a social and cultural impact. Culture can play an important role in life in various disciplines, not only in education but also in the world of work; culture has a significant direct impact on work motivation and performance of human resources. English also plays an important role in international business relations because English is an international language. Improving the quality of education, international business and human performance can also be affected by technology. One of these technologies is Artificial Intelligence helps the need for translation of English into the mother tongue used by teachers and students in learning English. Artificial intelligence has a significant impact on business performance.